Oil spill cleanup and response in Malaysian shorelines - Mohajeri, L. (2008)
The majority of oil spills (number of events) occur in coastal waters or in ports therefore, contamination of the shoreline is likely at most spills, and thus the issues of oil recovery and shoreline cleanup must be addressed. Nearly all shoreline cleanup methods have some kind of environmental impact. Hence selection of a cleanup method with minimum adverse impact on the environment is essential. For oil spill response and shoreline cleanup, there has been some innovation in the physical removal technologies since the 1970s. The only really new techniques developed in the last few years involve chemical and biological treatment methods. Bioremediation is one of the most costeffective, and environmentally-friendly methods to remediate different types of environmental pollutants. And in case of coastal sensitive areas (mangrove forests, coral reefs, wetlands, etc.) it is the only acceptable choice. This article discusses the need for application of bioremediation for Malaysian aquatic environment in case of oil spill and highlights management/engineering methods for hydrocarbon bioremediation in the country. Recommendations on the use of bioremediation for environmental management in case of oil spill have been made.